物体空间位置的实时测量方法研究 - 黄文鑫; 李明; 姜良银; 李伟; 田应仲 (Jixie chuandong)
The real-time object spatial locations in the fields of aircraft,ship and robot have to be measured and controlled.In the previous research on the object space attitude,Research on the measurement method and principles of the centre of space object step by step is carried out.The method is reliable and accurate which is proved by experiments.